2017
DOI: 10.1111/cge.13130
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a severity scoring system for Zellweger spectrum disorders

Abstract: The lack of a validated severity scoring system for individuals with Zellweger spectrum disorders (ZSD) hampers optimal patient care and reliable research. Here, we describe the development of such severity score and its validation in a large, well-characterized cohort of ZSD individuals. We developed a severity scoring system based on the 14 organs that typically can be affected in ZSD. A standardized and validated method was used to classify additional care needs in individuals with neurodevelopmental disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Based on the occurrence of early hearing loss and then bilateral cataracts and leukodystrophy on MR images, we could retrospectively categorize patient to be suffered from mild ZSD based on the severity scoring scale proposed by Klouwer et al (Klouwer et al 2018). As in our previously published case and report of Weller et al (Weller et al 2008), the leukoencephalopathy and brain atrophy are the commonest changes found in mildly affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the occurrence of early hearing loss and then bilateral cataracts and leukodystrophy on MR images, we could retrospectively categorize patient to be suffered from mild ZSD based on the severity scoring scale proposed by Klouwer et al (Klouwer et al 2018). As in our previously published case and report of Weller et al (Weller et al 2008), the leukoencephalopathy and brain atrophy are the commonest changes found in mildly affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exon boundaries were based on http://useast.ensembl.org. We assigned phenotypic severity scores to each patient where data was complete, adapting a previously published scoring system that was developed for a different, but similarly multi‐systemic, syndrome (Klouwer et al, 2018). An “overall phenotype severity” score was assigned, which combined degree of cognitive differences, presence or absence of major organ differences, and premature death (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…We also assigned growth severity scores based on current measurements using Z ‐scores, but only for our cohort of 12 patients, given their completeness of data regarding growth parameters. If a patient's growth parameter was 0 to −1 SD this received a score of 0; growth of −1 to −2 SD received a score of 1; less than −2 SD received a score of 2 (Klouwer et al, 2018). Therefore, using weight, height, and head circumference, a patient's growth score ranged from 0 to 6, with 6 being the most severe growth restriction.…”
Section: Methodsmentioning
confidence: 99%
“…Overviewing the neurological phenotype of these 13 patients, all patients had the well‐known symptoms of ZSD patients, such as developmental delay, hearing and visual impairment, and enamel hypoplasia. Zellweger severity scores and liver‐related symptoms are depicted in Table . Based on the symptoms of liver disease, we noticed two broad categories of liver phenotypes.…”
Section: Resultsmentioning
confidence: 99%